WD repeat domain 48 promotes hepatocellular carcinoma progression by stabilizing c‐Myc. Issue 23 (20th November 2022) - Li, Bo; Zhang, Ye‐wei; Cao, Kun; Li, Chao; Chen, Qian; Jiang, Yi‐heng; Luo, Lu‐ling; Zuo, Shi
Abstract: The role of protein members containing the WD40 repeat domain in many diseases, including cancer, is well documented. However, the role of WD repeat domain 48 (WDR48) in hepatocellular carcinoma (HCC) and its molecular basis remain to be further investigated. In the present study, we report that WDR48 is downregulated in clinical HCC samples and evaluate the relationship between its expression and clinical features of HCC. In vitro experiments showed that WDR48 positively regulated the proliferation, invasion and metastasis of HCC cells and in vivo experiments showed that downregulation of WDR48 significantly inhibited the tumorigenicity of HCC cells. Mechanistically, WDR48 binds to the proto‐oncogene transcriptional regulator c‐Myc and stabilizes c‐Myc expression by mediating its deubiquitination, thereby enhancing cell proliferation and EMT signalling. Our study demonstrates the oncogenic role of WDR48 and suggests that WDR48 can be an important target in HCC.